DAMPAK AKSELERASI DIGITAL TERHADAP PERILAKU KONSUMEN ASURANSI JIWA SELAMA PANDEMI COVID-19: PERAN KELOMPOK REFERENSI SEBAGAI VARIABLE MODERASI - Wikantari, Maria Assumpta (2021)
This study is being carried out with the aim of finding out if virtual accelerators have any power in motivating buyers to buy cover during the moderate COVID19 pandemic using a peer group. are not. This study is a descriptive quantitative study. This study used a full sampling approach as the sample was taken of one hundred bedding buyers during the COVID19 pandemic. Collect questionnaire usage statistics for respondents. Analyze the statistics used on this declaration using the Statistcal Package for SocialSciences (SPSS) software. Theimpact ofthis review is that there may be some strength between digital acceleration on consumer behavior, the benchmark group has no impact on consumer behavior. Meanwhile, if the peer-to-peer group mediates between digital acceleration and consumer behavior, it has devastating and far-reaching effects. Therefore, we can conclude that Reference Groups have digital acceleration power for consumer behavior. For the researchers assume that life insurance companies pay special attention to peer groups so they can increase their life insurance purchases during Covid19.